Direct evidence for dynamics of cell heterogeneity in watercored apples: turgor-associated metabolic modifications and within-fruit water potential gradient unveiled by single-cell analyses. (3rd August 2021) - Wada, Hiroshi; Nakata, Keisuke; Nonami, Hiroshi; Erra-Balsells, Rosa; Tatsuki, Miho; Hatakeyama, Yuto; Tanaka, Fukuyo
Abstract: Watercore is a physiological disorder in apple ( Malus   ×   domestica Borkh.) fruits that appears as water-soaked tissues adjacent to the vascular core, although there is little information on what exactly occurs at cell level in the watercored apples, particularly from the viewpoint of cell water relations. By combining picolitre pressure-probe electrospray-ionization mass spectrometry (picoPPESI-MS) with freezing point osmometry and vapor pressure osmometry, changes in cell water status and metabolisms were spatially assayed in the same fruit. In the watercored fruit, total soluble solid was lower in the watercore region than the normal outer parenchyma region, but there was no spatial difference in the osmotic potentials determined with freezing point osmometry. Importantly, a disagreement between the osmotic potentials determined with two methods has been observed in the watercore region, indicating the presence of significant volatile compounds in the cellular fluids collected. In the watercored fruit, cell turgor varied across flesh, and a steeper water potential gradient has been established from the normal outer parenchyma region to the watercore region, retaining the potential to transport water to the watercore region. Site-specific analysis using picoPPESI-MS revealed that together with a reduction in turgor, remarkable metabolic modifications through fermentation have occurred at the border, inducing greater production of watercore-related volatile compounds, such as alcohols and esters, compared with other regions. Because alcohols including ethanol have low reflection coefficients, it is very likely that these molecules would have rapidly penetrated membranes to accumulate in apoplast to fill. In addition to the water potential gradient detected here, this would physically contribute to the appearance with high tissue transparency and changes in colour differences. Therefore, it is concluded that these spatial changes in cell water relations are closely associated with watercore symptoms as well as with metabolic alterations.